Pseudoautotomy in Dendrophidion dendrophis and Mastigodryas bifossatus (Serpentes: Colubridae): Tail Morphology and breakage frequency - Dourado, Ângelo C. M.; Oliveira, Leonardo [UNESP]; Prudente, Ana L. C. (American Society of Ichthyologists and Herpetologists (ASIH), 2013)
The micro and macro structures of the caudal vertebrae and muscles of Dendrophidion dendrophis and Mastigodryas bifossatus were described using histological slides, dissections, radiographs, and clearing and double staining of intact, broken, and healed tails. To analyze the relationship among the frequencies of healed tails we established two populations of D. dendrophis and six groups of M. bifossatus. We found that fractures of the tail in the two species are intervertebral, and there are no morphological and/or structural mechanisms that facilitate the urotomy, which is classified as non-specialized pseudoautotomy. The caudal vertebrae of D. dendrophis and M. bifossatus show minor differences in the shape of the condyle, cotyle, and border of the neural spine, and in the size and orientation of the hemapophysis and pleurapophysis. The absence of bleeding at the moment of tail breakage may indicate the presence of sphincters in the veins and arteries of D. dendrophis. The distal part of the last vertebrae retained in healed tails of D. dendrophis and M. bifossatus participates in the healing processes as a possible source of calcium in the formation of a calcified cap. We found high frequency of tail breakage in both species, which occurs in almost the entire length of the tail, with no specific areas of concentration. There was no difference in the frequencies of healed tails among males and females of different populations of D. dendrophis and M. bifossatus. Juveniles have lower breakage frequencies than adults in both species, except for populations of M. bifossatus from the Cerrado and Pampa. © 2013 by the American Society of Ichthyologists and Herpetologists.
Keywords: calcium; concentration (composition); frequency analysis; histology; morphology; muscle; size; snake